Bio-Ethanol Production from Fruit and Vegetable Waste by Using Saccharomyces cerevisiae - Khandaker, Dr. Mohammad Moneruzzaman; Badaluddin, Dr. Noor Afiza; Mohd, Prof. Madya Ts. Dr. Khamsah Suryati (IntechOpen, 2021)
Waste from the food is a challenge to the environment all over the globe, hence there is need to be recycled. Vegetables and fruits biomass is a resource of renewable energy with significant fuel source potential for the production of electricity and steam, fuel for consumption and laboratory solvents. Bioethanol derived from biomass contributed 10–14% of the total world energy supply and solved the world crisis such as global warming and depletion of fossil fuel. Presently, bioethanol is a global issue on the efforts to reduced global pollution, contributed significantly by the petroleum or diesel combustion or combination of both. Vegetables and fruits waste significantly contains high sugar which can be utilized and serve as a raw material in the production of renewable energy using Saccharomyces cerevisiae. Though 80% of the current bioethanol are generated from edible materials such as starch and sugar. Biomass from lignocellulosic gathered more attention recently. The objective of this review is to account for the procedures involved in the production of bioethanol from biomass of fruits and vegetable waste through a fermentation process using Saccharomyces cerevisiae. In this chapter, we discussed the biomass preparation and fermentation techniques for bioethanol and reviewed the results of different fruits and vegetable waste. We found pineapple and orange fruit biomass contain a higher amount of bioethanol and easier to extract than the other fruit and vegetable wastes. Recent review coined out that dry biomass of fruit and vegetable is a promising feedstock in the utilization of bioethanol production.